A high-performance voltammetric methodology for the ultra-sensitive detection of riboflavin in food matrices based on graphene oxide-covered hollow MnO2 spheres. (1st August 2021) - Zhang, Lijun; Liu, Xian; Luo, Luyu; Hu, Cong; Fu, Jianwei; Chang, Xueping; Gan, Tian
Graphical abstract: Highlights: A simple voltammetric methodology is developed for riboflavin detection. Graphane oxide-reinforced hollow MnO2 nanospheres are employed for signal enhancement. Fast response and subnanomolar detection limit in riboflavin detection are achieved. Successful application of this method in complicated food matrices analysis. Abstract: A high-performance voltammetric methodology was developed to achieve ultra-sensitive detection of riboflavin, employing an electrode modified by graphene oxide-covered hollow MnO2 spheres nanocomposite with high catalytic activity, large surface area, and hierarchical layered structure. Under the optimal conditions, the current responses of the oxidation peak located at −0.39 V showed a good linear relationship versus the concentration of riboflavin in the range of 1.0 nM–4.0 μM in acetate buffer (pH 5.4). The limit of detection was determined as 0.26 nM. Moreover, the proposed electrode exhibited high reproducibility (relative standard deviation of 1.7%, n  = 10) and excellent stability (97.6% sensitivity within two months), which has been successfully applied to the quantification of riboflavin in complicated food matrices, with results in good accordance with those obtained by chromatography as a reference method, indicating it is an effective sensing platform for ultra-sensitive determination of riboflavin in practical applications.